2021
DOI: 10.1021/acsomega.1c02534
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Self-Sorting and the Realization of Ferroelectricity in the Columnar Liquid Crystal Phase of an Optically Inactive N,N′-Diphenylurea Derivative Possessing Six (±)-Citronellyl Groups

Abstract: An axially polar-ferroelectric columnar liquid crystal (AP-FCLC) phase that exhibits both switching and maintenance of the macro-polarity in the column axis direction has been achieved in an N,N′-bis(3,4,5-trialkoxyphenyl)urea compound (rac-1) prepared from (±)-citronellyl bromide. Although it had been thought that chirality is necessary to achieve the AP-FCLC phase from our previous study, the optically inactive compound which is a mixture of 21 stereoisomers, generated an AP-FCLC phase. We confirmed its ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
(63 reference statements)
0
12
0
Order By: Relevance
“…They were attributed to the Cr and Col r phases based on the presence or absence of a short-range order in the wide-angle region. In addition, the comparison of the electron density maps of the Cr and Col r phases (Figure S3) revealed that they have similar molecular packing structures. Then, by POM observation on heating (Figures , S4, and S5), two similar fan-shaped textures were observed before and after the Cr–Col r transition at 64 °C.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…They were attributed to the Cr and Col r phases based on the presence or absence of a short-range order in the wide-angle region. In addition, the comparison of the electron density maps of the Cr and Col r phases (Figure S3) revealed that they have similar molecular packing structures. Then, by POM observation on heating (Figures , S4, and S5), two similar fan-shaped textures were observed before and after the Cr–Col r transition at 64 °C.…”
Section: Resultsmentioning
confidence: 98%
“…To investigate the ferroelectricity of 1 , several SHG experiments were conducted. SHG measurement is an established method to confirm the macroscopic polarities of materials. ,,, Compound 1 was heated to its Iso state, introduced in a sample cell consisting of two glass plates coated with indium tin oxide and polyimide films (cell gap: 5 μm) (Figure S9) by capillarity, and cooled to room temperature. The obtained sample in the cell was used as the original sample in Figure a.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations